Biological Parameters and Feeding Potential of Micromus timidus Hagen (Neuroptera: Hemerobiidae) on Selected Aphid Species - S., Bhavana; Mulimani, Vidya; N., Sumithramma; Reddy, C. N. Lakshminarayana (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
In the present study, we investigated on the developmental biology, adult longevity and fecundity of Micromus timidus Hagen on Aphis craccivora (Koch), Aphis gossypii Glover, Rhopalosiphum maidis (Fitch) and Uroleucon compositae (Theobald) at room temperature (28±20C) and relative humidity of 70%. The study design followed was completely randomized design (CRD). The study was conducted with three replications with 10 larvae in each replication for biology studies and for adult parameters 3 replications with 10 pairs in each replication used. Shortest incubation period, II instar and III instar duration, total larval period, pre-pupal period, and egg to adult period of M. timidus were recorded on A. craccivora, shortest I instar duration was recorded on U. compositae and least pupal period on A. gossypii. The developmental periods for all trait were extended when fed on R. maidis. The reproductive traits viz., oviposition period and adult longevity (male and female) were maximum when M. timidus adults fed on A. gossypii, and the highest fecundity was recorded when fed on A. craccivora. Feeding potential in M. timidus increases progressively across successive instars, with III instar larvae exhibiting the highest aphid predation rate, and first instar larvae displaying the lowest feeding activity. The maximum feeding potential of the larva was noted on A. craccivora (142.47 ± 31.66), while, the adult feeding potential increased when it was given with A. gossypii (1335.10 ± 192.74).